Pengembangan Sumber Daya Aparatur Dinas Parawisata Provinsi Sulawesi Barat - Marzukli, Marzukli; Mappamiring, Mappamiring; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
The aim of this research is to determine the development of the tourism apparatus of the West Sulawesi Province.  This research uses  a qualitative description of research with the type of phenomenological research.  Informants in this research are 7 people.  Data collection techniques with in-depth interviews, direct observation and documentation.  The results of this research indicate that the activities of the apparatus resource development program have been carried out and run in accordance with the state civil service management procedures.  It has just a few obstacles in the development activities, namely from the aspects of: a) educational programs of the apparatus regarding the understanding of job duties and still there are some employees who are still confused, b) the training program of the apparatus has not been effective due to lack of interest of businessmeb to follow the activities  training provided by the West Sulawesi Provincial Tourism Office.  and c) career development for the apparatus has not been very effective in the process of employee career, sometimes overlapping, and those who are entitled to such ranks or classes and facilities for education and training are only certain people who have emotional closeness with superiors such as family, friends  , or kinship.